NIMG-02. 18F-FLUCICLOVINE POSITRON EMISSION TOMOGRAPHY TO DISTINGUISH TUMOR PROGRESSION FROM RADIATION NECROSIS FOLLOWING STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASIS: A QUALITATIVE ANALYSIS. (12th November 2021) - Smile, Timothy; Tom, Martin; Obuchowski, Nancy; DiFilippo, Frank; Jones, Stephen; Suh, John; Murphy, Erin; Yu, Jennifer; Mohammadi, Alireza; Barnett, Gene; Huang, Steve; Wu, Guiyun; et al.
Abstract: PURPOSE/OBJECTIVE(S): To assess the ability of 18 F-Fluciclovine PET/CT to distinguish radiation necrosis (RN) from tumor progression (TP) among patients with brain metastases (BM) treated with stereotactic radiosurgery (SRS) in a prospective pilot study. MATERIALS/METHODS: Adults with post-SRS BM presenting with follow-up brain MRI equivocal for RN versus TP underwent 18 F-Fluciclovine PET/CT within 30 days of equivocal MRI. PET images were reconstructed using a point-spread-function algorithm. Three physician reviewers independently performed qualitative analyses of each lesion using a three-point visual score relative to PET-avidity of blood pool and parotid. Quantitative metrics for each lesion were documented. Reference standard was clinical follow-up with brain MRI until tumor board consensus or tissue confirmation. Nonparametric estimates of area under the receiver operating characteristic curve (AUC) for clustered data were estimated, with diagnostic performance based on visual score. RESULTS: In 15 subjects with 20 lesions, final diagnosis was RN in 16 (80%) lesions and TP in 4 (20%). Visual score significantly correlated with final diagnosis (AUC range 0.836-0.906 [ p≤ 0.037]). A threshold score of 2 (lesion 18 F-fluciclovine uptake above blood pool to parotid) and higher produced sensitivities and specificities of 75-100% and 38-56% respectively among the reviewer majority. Conversely, a threshold of 3 (uptake higher than parotid) produced sensitivities and specificities of 50-75% and 100% respectively. CONCLUSION: In this prospective pilot, basic visual analysis of 18 F-Fluciclovine PET/CT provided high sensitivity and specificity in detection of TP in post-SRS BM based on different threshold scores, suggesting room for visual threshold optimization. A low TP event rate limited the ability to estimate sensitivity/specificity and to perform combined qualitative/quantitative analyses. Further study to refine interpretation criteria is ongoing.